BIOM-12. PROLONGED RESPONSE TO THIRD-LINE TREATMENT WITH COMBINATION CCNU/TMZ IN AN MGMT METHYLATED IDH-WILDTYPE GLIOBLASTOMA. (14th November 2022) - Pan, Peter; Haggiagi, Aya; Iwamoto, Fabio
Abstract: INTRODUCTION: Multiply recurrent glioblastoma suffers from poor response rates to treatment, and limited durability. We describe a case of an impressive response to third-line CCNU/TMZ. BACKGROUND: Headaches brought a 76-year-old man to medical attention. MRI identified an enhancing right temporal mass – path following resection demonstrated glioblastoma (IDH-wildtype, MGMT-methylated, TERT mutant; PTEN Y68H, CDKN2A/B loss, CCND3 amplification; VUS in POLE, ATM, GRIN2A, and ROS1). He received hypofractionated RT 40.05Gy/15-fractions plus 21-days concurrent TMZ 75 mg/m2, then 5-day-on / 23-day-off TMZ (150 mg/m2 cycles #1-3; 200 mg/m2 subsequent). MRI pre-cycle #6, nearly 6 months post-RT, showed increased enhancement/FLAIR consistent with local progression (POD).Second-Line: After screen-fail for clinical trial, initiated off-label regorafenib 160 mg/d, 21-days-on/7-days-off – with partial response in enhancement at 3 weeks. With dose-reduction to 120 mg/d cycles #2-3 (for mounting fatigue), enhancement progressively worsened. Despite resuming higher 160 mg/d for cycle #4, enhancement progressed, consistent with POD.Third-Line: Given presence of MGMT promoter methylation (and extrapolating from CeTeG/NOA-09), combination CCNU 100 mg/m2 (day 1) and TMZ 100 mg/m2 (days 2-6; 8-week cycle) was started. There was improvement in enhancement/FLAIR, which continued to improve gradually through 6 cycles of CCNU/TMZ. Durability of response was surprising – MRIs stable/improved at 15 months since starting CCNU/TMZ. DISCUSSION: This case illustrates impressive response to CCNU/TMZ in the third-line. Delayed RT treatment effect is less likely given time elapsed from RT at initial progression (after 5 cycles of adjuvant TMZ), convincing but short-lived improvement to regorafenib (that progressively worsened through 3 more regorafenib cycles), and robust response only with CCNU/TMZ. He was also never on steroids (except post-operatively) nor bevacizumab. This suggests that improvement was mediated by antitumor effect against progressing tumor, rather than delayed RT treatment effect. MGMT methylation may have played a role in this patient's response to dual alkylator therapy.